FAKTOR YANG MEMENGARUHI PRAKTIK PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR DI BEI - Regine Chandra; Liana Susanto (Jurnal Paradigma Akuntansi, 2023)
The aim of this study is to obtain empirical evidence regarding the effect of the independent variable which are financial leverage, firm size, managerial ownership, and institutional ownership on dependent variable, income smoothing practice. The sample on this research is limited on manufacturing companies listed on Indonesia Stock Exchange during the year 2017-2019. Data processing techniques examined by logistic regression and using Eviews 12 to process the data. The result of this researchwas firm size has a significant and negative impact on income smoothing, institutionalownership has a significant and positive impact on income smoothing, while financial leverage and managerial ownership have no significant impact on income smoothing.